THE OBJECTIVES OF SUSTAINABILITY REPORTING AND ACCOUNTING IN SHARIA - Fardiantye Bella Cendika; Tjiptohadi Sawarjuwono (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2021)
Sustainability reporting and accounting practices spread by thousands companies attract Muslim researchers’ to affirm the sharia foundation on this issue. The purpose of this study is to straighten the basic objectives of sharia sustainability accounting and reporting. The technique was discourse analysis, by identifying comparisons the thought flows of standart about conventional and sharia sustainability reporting and accounting which were then examined based on the Qur'an. The results showed, the basic objectives of sharia sustainability reporting and accounting are; (1) accountability and (2) introspection. The results of this study have a theoretical contribution to the justification of differences in the meaning of the basic objectives of reporting and conventional and Islamic sustainability accounting. The results of the research can be a motivation for the Financial Services Authority (OJK) together with the Sharia Accounting Standards Board (DSAS) and the Indonesian Ulema Council (MUI) to hasten the formulation of sharia sustainability reporting and accounting standards that are suitable with the conditions in Indonesia, making it easier for business people to learn and apply the concept of sharia reporting and accounting for sustainability.